2020
DOI: 10.3390/ma13225252
|View full text |Cite
|
Sign up to set email alerts
|

Composite and Surface Functionalization of Ultrafine-Grained Ti23Zr25Nb Alloy for Medical Applications

Abstract: In this study, the ultrafine-grained Ti23Zr25Nb-based composites with 45S5 Bioglass and Ag, Cu, or Zn additions were produced by application of the mechanical alloying technique. Additionally, the base Ti23Zr25Nb alloy was electrochemically modified in the two stages of processing: electrochemical etching in the solution of H3PO4 and HF followed by electrochemical deposition in Ca(NO3)2, (NH4)2HPO4, and HCl. The in vitro cytocompatibility studies were also done with comparison to the commercially pure titanium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 67 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…The aim of the current study is directed at improving the physicochemical and mechanical properties as well as biocompatibility of Ti-based systems through crystal structure evolution (α → β) and new microstructure formation (micro → nano or ultrafine) via its chemical composition modification and processing method, respectively [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. β-type titanium alloys are interesting biomaterials for innovative implantable medical devices.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The aim of the current study is directed at improving the physicochemical and mechanical properties as well as biocompatibility of Ti-based systems through crystal structure evolution (α → β) and new microstructure formation (micro → nano or ultrafine) via its chemical composition modification and processing method, respectively [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. β-type titanium alloys are interesting biomaterials for innovative implantable medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…β-type titanium alloys are interesting biomaterials for innovative implantable medical devices. Recently studies on TiMo, TiNb, TiZrNb, TiNbHf, TiNbZrTa, TiNbZrTaSiFe have confirmed their interesting properties for future application in medicine [ 9 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. It is important to note, that the cytotoxicity of Mo, Zr, and Nb is lower than that for commercial purity Ti [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations